N2-foam-assisted CO2 huff-n-puff process for enhanced oil recovery in a heterogeneous edge-water reservoir: experiments and pilot tests. Issue 2 (4th January 2021) - Hao, Hongda; Hou, Jirui; Zhao, Fenglan; Huang, Handong; Liu, Huaizhu
Abstract : Edge water and gas can be temporarily delayed with the assistance of stable N2 foam. The oil recovery enhanced by N2 -foam-assisted CO2 huff-n-puff was twice that by pure CO2 huff-n-puff. Abstract : The CO2 huff-n-puff process is an effective method to enhance oil recovery; however, its utilization is limited in heterogenous edge-water reservoirs due to the severe water channeling. Accordingly, herein, a stable N2 foam is proposed to assist CO2 huff-n-puff process for enhanced oil recovery. Sodium dodecyl sulfate (SDS) and polyacrylamide (HPAM) were used as the surfactant and stabilizer, respectively, and 0.3 wt% of SDS + 0.3 wt% of HPAM were screened in the laboratory to generate a foam with good foamability and long foam stability. Subsequently, dynamic foam tests using 1D sand packs were conducted at 65 °C and 15 MPa, and a gas/liquid ratio (GLR) of 1 : 1 was optimized to form a strong barrier in high permeable porous media to treat water and gas channeling. 3D heterogeneous models were established in the laboratory, and N2 -foam-assisted CO2 huff-n-puff experiments were conducted after edge-water driving. The results showed that an oil recovery of 13.69% was obtained with four cycles of N2 -foam-assisted CO2 injection, which is twice that obtained by the CO2 huff-n-puff process. The stable N2 foam could temporarily delay the water and gas channeling, and subsequently, CO2 fully extracted the remaining oil in the low permeable zones around the production well. Pilot tests were conducted in 8 horizontal wells, and a total oil production of 1784 tons with a net price value (NPV) of $240 416.26 was obtained using the N2 -foam-assisted CO2 huff-n-puff process, which is a profitable method for enhanced oil recovery in heterogenous reservoirs with edge water.